Interpretasi Penaklukan Kota Yerikho dalam Yosua 6:1-27 Menurut Origenes - Mite, Luccianus Oktavianus (Divinitas Jurnal Filsafat dan Teologi Kontekstual, 2023)
Stories of violence in Scripture are often used as an excuse to commit acts of violence. This is a serious threat to life. Moreover, stories like this give rise to many negative interpretations. The story of Joshua 6:1-27 describes in detail the narrative of violence. It features Joshua and God as the main characters (cf. Josh 6:27). Joshua commands his people to attack and destroy the city of Jericho, killing all its inhabitants. Through a literature study, this paper will discuss the interpretation of Joshua 6 in the view of Origenes the Church Father. In his opinion, Joshua is not a historical figure but the typos of Jesus. Origenes says that the book of Joshua does not so much show the deeds of Joshua the son of Nun as it shows us the mystery of Jesus the Lord.AbstrakKisah kekerasan dalam Kitab Suci sering dijadikan alasan untuk melakukan tindak kekerasan. Ini menjadi ancaman serius dalam kehidupan. Apalagi kisah seperti ini memunculkan banyak tafsiran yang negatif. Kisah Yosua 6: 1-27 menggambarkan secara rinci mengenai narasi kekerasan. Ditampilkan Yosua dan Tuhan sebagai pemeran utama (bdk. Yos 6:27). Yosua memerintahkan bangsanya untuk menyerang dan menghancurkan kota Yerikho, lalu membunuh semua penduduknya. Melalui studi pustaka, makalah ini hendak membahas tafsiran Yosua 6 dalam pandangan para Bapa Gereja Origenes. Yosua bukanlah tokoh sejarah tetapi sebagai the typos of Jesus. Origenes mengatakan bahwa kitab Yosua tidak begitu banyak menunjukkan perbuatan-perbuatan anak Nun, melainkan menunjukkan kepada kita misteri Yesus Tuhan.